ZatLab: Gesture Recognition Framework for Artistic Performance Interaction – Overview - Baltazar, André (2018)
The main problem this paper addresses is the real-time recognition of gestures, particularly in the complex domain of artistic performance. By recognizing the performer gestures, one is able to map them to diverse controls, from lightning control to the creation of visuals, sound control or even music creation, thus allowing performers real-time manipulation of creative events. The work presented here takes this challenge, using a multidisciplinary approach to the problem, based in some of the known principles of how humans recognize gesture, together with the computer science methods to successfully complete the task. Therefore, this paper describes a gesture recognition framework developed with the goal of being used mainly in artistic performance domain. First one will review the previous works done in the area, followed by the description of the framework design and there is also the review of two artistic applications of the framework. The overall goal of this research is to foster the use of gestures, in an artistic context, to the creation of new ways of expression.